Surveillance of antibiotic use and resistance in Orthopaedic Department in an Egyptian University Hospital - Hassan, Azza Mahmoud; Ibrahim, Omaima; El Guinaidy, Magdy (International Journal of Infection Control, 2010)
Antimicrobial use and subsequently antimicrobial resistance among bacterial pathogens is a global problem, but in Egypt data are sparse. Orthopaedic departments reflect this problem because in them surgery constitutes the main manipulation and septic diseases constitute common complications both need guided antimicrobial therapy otherwise antimicrobial resistance will emerge. In order to highlight these issues, a prospective 9-month study on antimicrobial use and the antimicrobial susceptibility patterns of the isolated organisms in Orthopaedic Department, Tanta University, Egypt was carried out. High antimicrobial prescription rates (98.1%) with low rates of appropriateness (11.3%) were detected. Eighty-one percent of prescribed antimicrobial agents belong to cephalosporins and penicillins classes. Antibiotics were given for prophylaxis continued post-operatively (77%), for infections (13.4%) as well as randomly (22%). High rates of resistance were found in most of the bacteria studied. 53.3% of Staphylococcus aureus (S. aureus) and 66.7% of coagulase-negative staphylococcus (CNS) isolates were oxacillin resistant. Multi-resistant strains represented 48.6% of the isolated gram negative strains of which 29.2% were ESBL (Klebsiella 62.5% and E. coli 33.3%) while 19.4% were MR Pseudomonas and Acinetobacter isolates. Antibiotic treatment in our Orthopaedic Department appears to be substantial. Increasing and justifying efforts are needed to improve appropriateness of antimicrobial therapy and minimize the development of antimicrobial resistance. We also call for a nationwide surveillance programme to monitor microbial trends and antimicrobial resistance patterns in Egypt.